AB1283-HPR GASTROINTESTINAL INVOLVEMENT AND QUALITY OF LIFE IN A COHORT OF SYSTEMIC SCLEROSIS (SSC) PATIENTS. (13th June 2020) - El Aoufy, K.; Antola, I.; Sciortino, C.; Bellando Randone, S.; Guiducci, S.; Furst, D.; Matucci-Cerinic, M.
Abstract : Background: SSc is an autoimmune disease characterized by fibrosis of the skin and several internal organs involvement. The gastro intestinal tract is often affected causing a wide symptomatology that can involve the oesophagus, stomach and/or intestine. Objectives: To assess the gastro-intestinal tract with the UCLA SCTC GIT 2.0 questionnaire and the adherence to the Mediterranean diet with the Mediterranean Diet Score in a cohort of SSc patients. Methods: 18 SSc patients classified with ACR/EULAR criteria (limited and diffuse subsets) were enrolled from January to April 2019, from the outpatient clinic of the University of Florence, Division of Rheumatology, Careggi Hospital. UCLA SCTC GIT 2.0 questionnaire for gastro-intestinal involvement (range 0-3), Mediterranean Diet Score (MDS range 0-14) for adherence to the Mediterranean diet, Health Assessment Questioning (range 0-3) for disability and SF-36 (range 0-100) for the quality of life were administered to patients. Data on weight and height were collected for the calculation of the Body Mass Index (BMI). Results: the 18 SSc patients included had an average BMI of 23.9 ± 4.7 (M ± SD): only one patient was underweight (BMI=16.6) and 4 patients were overweight (BMI> 25). O ur results show good adherence to the Mediterranean diet with a score of 9.78 ± 2.24 (M±SD) to the MDS. The quality of life assessed by SF-36 show scores were below the cut-off (<50), showing an impaired quality of general life (mental summary index = 36.32 ± 11.35 and physical summary index = 39.53 ± 8.61). Patients disability, assessed by HAQ, reports some difficulty in carrying out daily life activities due to the disease (0.52 ± 0.53- M ± SD). Gastro-intestinal involvement, measured with the UCLA GIT 2.0 questionnaire, shows moderate symptoms (0.50-1.00) in most items (reflux, abdominal distension, social function and emotional well-being), while a lower score (0.00-0.49) it was found in other items (diarrhea, constipation and faecal incontinence). Therefore, the total score of gastrointestinal involvement is moderate (0.42 ± 0.38 M ± SD). Conclusion: In SSc, Gastrointestinal involvement has a significant impact on quality of life, influencing the eating habits and sometimes leading to nutritional deficiencies. Further studies to analyse the eating habits of SSc patients are needed. References: [1]Wojteczek A, Dardzińska JA, Małgorzewicz S, Gruszecka A, Zdrojewski Z. Prevalence of malnutrition in systemic sclerosis patients assessed by different diagnostic tools.Clin Rheumatol. 2020 Jan;39(1):227-232. doi: 10.1007/s10067-019-04810-z. Epub 2019 Nov 16. [2]McMahan ZH Gastrointestinal involvement in systemic sclerosis: an update. Curr Opin Rheumatol. 2019 Nov;31(6):561-568. doi: 10.1097/BOR.0000000000000645. [3]Smith E, Pauling JD The efficacy of dietary intervention on gastrointestinal involvement in systemic sclerosis: A systematic literature review.Semin Arthritis Rheum. 2019 Aug;49(1):112-118. doi: 10.1016/j.semarthrit.2018.12.001. Epub 2018 Dec 6. Disclosure of Interests: Khadija El Aoufy: None declared, Irene Antola: None declared, Costanza Sciortino: None declared, Silvia Bellando Randone: None declared, Serena Guiducci: None declared, Daniel Furst Grant/research support from: AbbVie, Actelion, Amgen, BMS, Corbus Pharmaceuticals, the National Institutes of Health, Novartis, Pfizer, and Roche/Genentech, Consultant of: AbbVie, Actelion, Amgen, BMS, Cytori Therapeutics, Corbus Pharmaceuticals, the National Institutes of Health, Novartis, Pfizer, and Roche/Genentech, Speakers bureau: CMC Connect (McCann Health Company), Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Bristol-Myers Squibb, Speakers bureau: Acetelion, Lilly, Boehringer Ingelheim